Russian «Great Capitalist Revolution »: is it over? - V. D. Solovej (Vestnik MGIMO-Universiteta, 2009)
The article covers the problem of an adjusting the new generation of theories of revolutions to today’s Russian’s reality. It discovers, whether the main factors of revolutionary situation in Russia exist. The conclusion is that possibility of a great government crisis is significant, its dynamics and consequences are unpredictable.